Optimizing vocational students' skills through adaptive online courses - Hutabarat, Sylvia Margareth; Purba, Sukarman; Purba , Saut (Institute of Computer Science (IOCS), 2024)
Vocational schools aim to provide teaching and training to students to prepare them for the job market. This article examines the effectiveness of adaptive online courses in assisting vocational schools to improve the skills of Vocational High School (SMK) students. Using a qualitative approach, this research analyzes various relevant literatures to understand how adaptive online courses can be implemented. This research intends to maximize students' personal skills with adaptive online courses. The results obtained from this study indicate that adaptive online courses have great potential to improve the skills of SMK students, especially in the context of personalized and industry-relevant learning.